FENOMENA NIKAH SIRRI DITENGAH MASYARAKAT: STUDI KASUS DI DESA SEKOTONG TENGAH KECAMATAN SEKOTONG LOMBOK BARAT - Sulsi Suparwadin Anwar; Ahmad Subekti; Humaidi Adi Kahari (Jurnal Hikmatina, 2021)
Sirri marriage is a legally valid marriage because it fulfills the pillars and conditions of marriage. However, because there is no written evidence in the form of a marriage certificate, it is still illegal under state law. The implementation of sirri marriages will have an impact in the future in their marital affairs in the form of child custody, property rights in the event of divorce in the future. Covering the area that the author will examine, the middle Sekotong village, Sekotong sub-district, West Lombok, there are still many marriages that are carried out in a sirri. The actions taken by the people of the village of Sekotong Tengah, Sekotong sub-district, West Lombok, must be based on the factors that cause them to carry out sirri marriages. The results of the study show that: (1) The implementation of sirri marriage is carried out according to the customs that apply in sekotong Tengah. Some of the Facts and Reasons for Sirri Marriage in Indonesian people's lives, are reality, the reasons ranging from the high cost of registering marriages to personal reasons that must be kept secret. The wedding will be held as usual, inviting many people from relatives to neighbors. The event is carried out the same as a wedding in general, except that it is not registered with the KUA. (2) The factors that cause unregistered marriages, there are many reasons why the marriage was carried out, namely: Because it was an application. To save costs and avoid administrative procedures that are considered cumbersome. Because the future wife is already pregnant out of wedlock. One of the bride and groom is not old enough to get married through KUA. (3) the impact of sirri marriage is: for the wife, it is not legal in the eyes of the law, automatically will not be able to get an inheritance from her husband and cannot also sue her husband because he is not given a living. For his son, his father's name could not be written on the birth certificate, and others would doubt if he had a real father. As for her husband, he will feel free in the eyes of the law, because there are no dependents on his wife and children.